Optimizing vaccine-induced CD8+ T-cell immunity: focus on recombinant adenovirus vectors. (September 2011) - Bassett, Jennifer D; Swift, Stephanie L; Bramson, Jonathan L
Recombinant adenoviruses have emerged as promising viral vectors for CD8 + T-cell vaccines. Our studies have indicated that unlike most acute infections, the CD8 + T-cell memory population elicited by recombinant human adenovirus serotype 5 (rHuAd5) displays a dominant effector memory phenotype. Persistent, low-level transgene expression from the rHuAd5 vector sustains the CD8 + T-cell memory population and a nonhematopoietic cell compartment appears to be involved in long-term presentation of adenoviral antigens. Although we are beginning to learn more about the factors that control the maintenance and functionality of memory CD8 + T cells, we do not yet fully understand what comprises a protective CD8 + T-cell response. Results from upcoming Phase II clinical trials will be important for determining whether rHuAd5 T-cell vaccines are effective in humans and should help identify correlates of CD8 + T-cell protection.